Assessment of physical properties and antimicrobial activity of activated charcoal impregnated with silver nanoparticles against Escherichia coli - Katwal, Rubina; Dhakal, Surakshaya; Rai, Suman; Chaudhary, Sujan (Himalayan Journal of Science and Technology, 2022)
Activated charcoal possesses small pores that help in the increment of the surface area available for chemical reactions. In this study, coal samples were taken from Kalimati, Dharan, and Eastern Nepal with the goal of determining the antibacterial activity of activated charcoal against Escherichia coli. This study also measured the moisture content, volatile substances, fixed carbon, and pH of coal using proximate analysis. This study was carried out by the activated carbon impregnation with silver nanoparticles by varying with the different AgNO3 concentrations: a) 0.1 mol/liter (mol/L) b) 1 mol/L c) 1.5 mol/L one at a time. By the proximate analysis, it was found that the moisture content was 2.2%, the volatile matter was 15%, the fixed carbon was 53.8%, and the pH was 5.83. The antimicrobial activity was performed by agar well diffusion methods. With 25 mg nanoparticles the zone of inhibition against E. coli was found to be 7 mm, 8 mm and 10 mm respectively and with 50 mg nanoparticles the zone of inhibition against E. coli was found to be 9 mm, 9 mm and 12 mm with concentration 0.1 mol/L, 1 mol/L and 1.5 mol/L of AgNO3 respectively. According to Pearson correlation (r = 0.697) and a simple linear regression (R2 = 0.798), there was a positive relationship between the concentration of AgNO3 and the zone of inhibition observed against E. coli. The highest zone of inhibition (ZOI) of activated charcoal impregnation against E. coli was 12 mm at 1.5 mol/L of AgNO3 with 50 mg silver nanoparticles, which was comparatively less against seven standard antibiotics (13-29 mm ZOI).